Peran Locus of Control dan Stres Kerja terhadap Kepuasan Kerja karyawan - Lisnawati Lisnawati; Acep Samsudin; Dicky Jhoansyah (IPM2KPE, 2019)
The purpose of this study is to measure how much influence the Locus of Control and job stress on employee job satisfaction at PT. Indomarco Adiprima, Sukabumi City. The research method used is descriptive and associative methods. The analysis technique used is the validity test, reliability test, multiple linear regression analysis, including the test of the coefficient of determination, multiple correlation coefficients and hypothesis testing using a stimulatory test (F test). The results of the test of the coefficient of determination (R2) Locus of Control and Work Stress affect the remaining 40.6% 59.4% influenced by other factors outside the study. Conclusions, Locus of Control and Job Stress significantly influence Employee Job Satisfaction. Keywords: Locus of Control, Job Stress, Employee Job Satisfaction